The relationship between these temporal characteristics of micro-explosive breakup of water/fuel composite droplets and the ambient gas temperature; International Communications in Heat and Mass Transfer; Vol. 164, Pt. A - Antonov D. V. Dmitry Vladimirovich; Fedorenko R. M. Roman Mikhaylovich; Vysokomornaya O. V. Olga Valeryevna; Yanovsky (Yanovskiy) Leonid Samoylovich L. S.; Strizhak P. A. Pavel Alexandrovich (2025, 2025)
Title screen